2019
DOI: 10.23889/ijpds.v4i3.1329
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Personal Care Services in Scotland: the Influence of Unpaid Carers

Abstract: Scotland is unique in its collection of routine data for all individuals in receipt of social care services. This care encompasses home and personal care services, down to telecare and meals services. As the Scottish population continues to age and local authorities stretch shrinking budgets over an increasing number of people, there is a pressing need to understand how older people use these services to ensure they are delivered in an efficient and effective way. The availability of administrative data in Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Expanding the mandatory years of schooling has improved educational achievement (Haegeland, Raaum and Salvanes, 2012), and reduced teen pregnancies (Black, Devereux and Salvanes, 2008). 34 The literature on health effects of public investments in children and youth is sparser, most likely due to data availability, and the majority of recent work comes from Sweden. Siflinger and van den Berg (2020) find that expanding day care availability decreases the prevalence of infectious diseases and reduces behavioral disorders and mental health problems by ages 6-7.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding the mandatory years of schooling has improved educational achievement (Haegeland, Raaum and Salvanes, 2012), and reduced teen pregnancies (Black, Devereux and Salvanes, 2008). 34 The literature on health effects of public investments in children and youth is sparser, most likely due to data availability, and the majority of recent work comes from Sweden. Siflinger and van den Berg (2020) find that expanding day care availability decreases the prevalence of infectious diseases and reduces behavioral disorders and mental health problems by ages 6-7.…”
Section: Discussionmentioning
confidence: 99%
“…While unpaid care may act as a substitute for professional home support for many people, more recent evidence has highlighted a more nuanced relationship between unpaid and professional care. Recent evidence from Scotland (where public home support is free) found that having an unpaid carer was actually related with an increase in professional home support provided, by 1 hour and 14 minutes weekly (Lemmon, 2020). The authors argue that the findings may be a result of a number of factors, including the possibility that home support recipients without an unpaid carer to advocate for them may have insufficient home support to meet their needs.…”
Section: Unpaid and Family Carementioning
confidence: 94%
“…At present several Scottish Government/ESRC-funded PhD projects have applied for and been granted access to link the SCS to various health datasets with results pending. These include projects aiming to identify the relationships between multimorbidity and social care [15] and to ascertain the influence of unpaid carers for those receiving personal care services [16]. No academic studies have been completed with the SCS as a stand-alone resource.…”
Section: Usage To Datementioning
confidence: 99%